2023
DOI: 10.3389/fnins.2023.1232670
|View full text |Cite
|
Sign up to set email alerts
|

Age-related decline in cognitive flexibility is associated with the levels of hippocampal neurogenesis

Evgeny M. Amelchenko,
Dmitri V. Bezriadnov,
Olga A. Chekhov
et al.

Abstract: Aging is associated with impairments in learning, memory, and cognitive flexibility, as well as a gradual decline in hippocampal neurogenesis. We investigated the performance of 6-and 14-month-old mice (considered mature adult and late middle age, respectively) in learning and memory tasks based on the Morris water maze (MWM) and determined their levels of preceding and current neurogenesis. While both age groups successfully performed in the spatial version of MWM (sMWM), the older mice were less efficient co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…We produced a dataset of conditioned fear memory (GN trait ID: 5XF_10474) with 14 month old B-BXD animals from 42 different strains ( Figure 5A ). At this age, PGBs are present in the B6 hippocampus and age-related behavioral alterations such as reduced CFM become apparent (Amelchenko et al, 2023; Hamieh et al, 2021; Jucker et al, 1992; Wu et al, 2015). Importantly, no correlation was found between CFM (time spent frozen) and PGB density in the subset of overlapping strains ( n = 13) ( Figure 5B,C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We produced a dataset of conditioned fear memory (GN trait ID: 5XF_10474) with 14 month old B-BXD animals from 42 different strains ( Figure 5A ). At this age, PGBs are present in the B6 hippocampus and age-related behavioral alterations such as reduced CFM become apparent (Amelchenko et al, 2023; Hamieh et al, 2021; Jucker et al, 1992; Wu et al, 2015). Importantly, no correlation was found between CFM (time spent frozen) and PGB density in the subset of overlapping strains ( n = 13) ( Figure 5B,C ).…”
Section: Resultsmentioning
confidence: 99%
“…To mitigate this limitation, we performed conditioned fear memory (CFM) tests on aged B-BXDs, which again yielded no evidence suggesting negative effects of PGBs on cognition. Studies have shown that CFM is a effective readout of hippocampal function in spatial memory and learning confidence (Amelchenko et al, 2023; Hernández-Mercado and Zepeda, 2022) and have been demonstrated to deliver readable outcomes in cognitive performance tests in an age related context (Hamieh et al, 2021; Hernández-Mercado and Zepeda, 2022; Verbitsky et al, 2004; Wu et al, 2015). Although we cannot exclude an effect of PGBs on cognition at geriatric stages, we conclude it is unlikely that age-related PGB burden in the hippocampus has a strong negative effect on cognitive function up to 18-months of age.…”
Section: Discussionmentioning
confidence: 99%